Synthesis and enhancement on structural, compressive strength and microhardness of 45S5 based bioactive glasses - Loh, Zhi Wei; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Cheong, Wei Mun (Springer Science and Business Media B.V., 2023)
The xCaF2–45SiO2–25CaO–10B2O3–10Na2O–(10-x)P2O5 based 45S5 bioactive glass, where x = 0, 2, 4, 6, 8 and 10 wt.%. have been fabricated by modified melt-quenching method. X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) measurement indicate that the CaF2 addition into the SiO2–CaO–B2O3–Na2O–P2O5 glass increases the stability of the amorphous phase and not lead to the crystallization of the glasses. The field emission scanning electron microscopy (FESEM) micrographs and energy dispersive X-ray (EDX) analysis presented the non-uniform particle distribution and the amorphous glassy structure in all glass samples. The compressive strength (CS) of the glass samples increases with CaF2/P2O5 ratios from 46.80 ± 0.15 MPa to 48.98 ± 0.11 MPa. However, the decrement occurs when further increment in CaF2/P2O5 ratios, which is caused by the excessive CaF2 content in the glass structure. Vickers microhardness (VM) shows a similar trend, increasing from 2.00 ± 0.07 GPa to 3.09 ± 0.07 GPa and suddenly decreasing with the higher addition of CaF2 concentration. Consequently, the BG3F glass sample presents optimum conditions for physical and mechanical performance comparable to the human enamel.